Solar‐Energy Harvesting: Broadband Hot‐Electron Collection for Solar Water Splitting with Plasmonic Titanium Nitride (Advanced Optical Materials 15/2017). Issue 15 (2nd August 2017) - Naldoni, Alberto; Guler, Urcan; Wang, Zhuoxian; Marelli, Marcello; Malara, Francesco; Meng, Xiangeng; Besteiro, Lucas V.; Govorov, Alexander O.; Kildishev, Alexander V.; Boltasseva, Alexandra; Shalaev, Vladimir M.
Abstract : In article number1601031, Alberto Naldoni, Vladimir M. Shalaev, and co‐workers present plasmonic titanium nitride (TiN) nanoparticles on top of TiO2 nanowires, which strongly improve the activity toward photoelectrochemical water splitting. Plasmonic TiN provides efficient generation of hot electrons due to a broadband absorption and improved electrical compatibility at the TiN–TiO2 interface.